Bathymetry of the Aleutian and Bowers Basin, Bering Sea - U.S. Geological Survey (USGS Science Data Catalog, 1997)
This coverage contains bathymetric contours for Aleutian Basin and Bowers Basin east of the 1867 Convention Line in the southwestern Bering Sea. Geographic extent of this file is: 51.7 : 62.0 N / -165.1 W : 170.0 E. Bathymetric contours range from 50 m to 6400 m. This coverage was used to display the bathymetry for the Atlas of the U.S. Exclusive Economic Zone, Bering Sea, U.S. Geological Survey Misc. Investigations Series I-2053, 1991 (also known as the GLORIA survey). The map was published separately by Hall et al. 1989, U. S. Geological Survey Open-file Report 89-548.